Harverting: easy separate / Amru Ziyad Nafiz Zahare, Muhammad Firdaus Fikri Masud and Ahmad Haikal Ahmad - Zahare, Amru Ziyad Nafiz; Masud, Muhammad Firdaus Fikri; Ahmad, Ahmad Haikal (Faculty of Plantation and Agrotechnology, 2023)
Malaysia is the country who planting paddy as their main crop due to good environmental and as a main consumption for all people. By the way, the increasing the population tend to decreasing the food resource. From the issue, government will take the data especially for rice paddy to estimate the yield in every state as their reference either the food supply is still insufficient or not. The agency under the government which is Department of Agriculture will estimate the yield every harvesting season. By the way, the process of estimating paddy sometime is not accurate. It is because, the process of separating paddy which make by the Department of Agriculture is by using manual method. As a result, some rice not dissolved and make the data be less aqurate. The purpose of the study is to create the tool that can dissolved all the selected paddy rice. the tool is like a pipe but can be open and close. The method is by opening the tool and put some paddy in it, close and the lastly pull out the paddy. The rice and paddy plant will separate without making any undissolved rice paddy. In conclusion, this will continuously increase and will take percentage of expected count of grains.